2019
DOI: 10.5479/si.0077-5630.620
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Changes in the Coral Reef Communities of Indonesia's Bali Barat National Park, 2011–2016

Abstract: The coral reefs of Bali Barat National Park, one of Indonesia’s oldest marine protected areas, are known for their high biodiversity and excellent sport diving; however, stressors such as destructive fishing practices, elevated water temperatures, damage from anchors and careless visitors have been observed on these reefs for decades. The purpose of this study was to document and quantify changes in the fish and stony coral community structure of reefs within and outside the boundaries of Bali Barat National P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…Somehow, this condition was also found in the other coastal area in Indonesia (Heery et al, 2018;Annas et al, 2017;Fadli et al, 2014;Fadli et al, 2012;Baird et al, 2012;Kusuma et al, 2016). Reef degradation in Indonesia mainly was caused by land-based pollution and human activities (Edinger and Risk, 2000;Baum et al, 2015;Annas et al, 2017;Putra et al, 2018;Suparno et al, 2019). The degradation also affected seagrass meadows (Short et al, 2014) and mangrove forests ecosystem (Das-Gupta and Shaw, 2013).…”
Section: Introductionmentioning
confidence: 77%
“…Somehow, this condition was also found in the other coastal area in Indonesia (Heery et al, 2018;Annas et al, 2017;Fadli et al, 2014;Fadli et al, 2012;Baird et al, 2012;Kusuma et al, 2016). Reef degradation in Indonesia mainly was caused by land-based pollution and human activities (Edinger and Risk, 2000;Baum et al, 2015;Annas et al, 2017;Putra et al, 2018;Suparno et al, 2019). The degradation also affected seagrass meadows (Short et al, 2014) and mangrove forests ecosystem (Das-Gupta and Shaw, 2013).…”
Section: Introductionmentioning
confidence: 77%
“…In contrast, the northern Great Barrier Reef experienced 50% loss of live coral cover in 8 months during the 2016 bleaching event, with heavily bleached reefs undergoing a shift in coral assemblages from habitat forming branching and tabular species to species with less complex morphologies [ 29 ]. Similarly, 3 global bleaching events between 2011–2016, the most significant of which was in January 2016, resulted in a 44% decline in live coral cover in Indonesia’s Bali Barat National Park [ 30 ]. However, unlike the Great Barrier Reef, loss of coral cover in Indonesia was not accompanied by declines in taxonomic (genus) richness [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 3 global bleaching events between 2011–2016, the most significant of which was in January 2016, resulted in a 44% decline in live coral cover in Indonesia’s Bali Barat National Park [ 30 ]. However, unlike the Great Barrier Reef, loss of coral cover in Indonesia was not accompanied by declines in taxonomic (genus) richness [ 30 ]. Reef-building capacity (percentage cover of reef building organisms: hard corals and coralline algae [ 31 ]), a proposed indicator of the resilience of reefs to large-scale disturbances, was also high across our study sites.…”
Section: Discussionmentioning
confidence: 99%
“…More recent data from 2017 has highlighted similar results, suggesting that 50% of its corals are in good health, whilst 20% are declining and 30% are poor (Marine and Fisheries O ce 2017 data, as cited by 43 . The primary reasons for declines in Bali's coral reef health are associated with coral bleaching [44][45][46] and destructive shing practices 47,48 , although multiple other threats also persist.…”
Section: The Coral Reefs Of Bali Indonesiamentioning
confidence: 99%
“…Recent data from 2017 has shown that that 50% of Bali's corals are in good health, whilst 20% are declining and 30% are poor 43 . The primary reasons for declines in Bali's coral reef health are associated with climate change-induced coral bleaching [44][45][46] and destructive extractive practices such as over shing and coral mining 47,48 . Whilst some threats to Bali's reefs, such as bleaching, appear to be widespread [43][44][45][46] , others, such as destructive extractive practices, have been shown to vary regionally across the island 48 .…”
Section: Changes To the Marine Environmentmentioning
confidence: 99%